ANALISIS KEBUTUHAN PEGAWAI BERDASARKAN PERHITUNGAN BEBAN KERJA PEGAWAI (STUDI KASUS: FAKULTAS SAINS DAN TEKNOLOGI UIN SYARIF HIDAYATULLAH JAKARTA) - Elvi Fetrina (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2017)
UIN Syarif Hidayatullah Jakarta is one of the highest educational institutions that actively participate inundergraduate, master and doctoral programs with large numbers from year to year. The number of students isvery much from year to year, spread to various faculties owned by UIN Syarif Hidayatullah Jakarta, Faculty ofScience and Technology (FST), which is from 2548 active students until 2014. With a large number of collegestudents, who owned by the FST program is too large to be able to produce effective services to the students soit is not surprising that the complaints given by students to the study program, which is considered less responsive in the students' view, as the students complained to the Faculty in 2016 ini.Hal very want to know how about working in this case the secretary of FST program, to serve students with FTE (Full Time Equivalent) method. This method can provide information about what is needed in the categorize into normal, overload or underloadnya work from the secretary prodi.